Current aptitude under climate change scenarios for three crops in Mexico - Gómez Díaz, Jesús D.; Flores Velázquez, Raquel; Monterroso Riva, Alejandros I. (Revista Mexicana de Ciencias Agrícolas, 2020)
For the agricultural land area of Mexico, the areas with different degrees of aptitude for corn, sorghum and wheat were determined, all under temporary conditions, for the current conditions and with climate change scenarios estimated with the GFDL, HAGDEM and REA models; for the RCP of 4.5 and 8.5 W m-2. The proportion of agricultural land with some degree of aptitude for current conditions is as follows: corn 81.59%, sorghum 61.54% and wheat 26.95%. Of the climatic variables that determine the lack of aptitude in corn and wheat in agricultural areas, it is mainly the annual mean temperature alone or in combination with the precipitation, in sorghum it is mainly the annual mean precipitation alone or in combination with the annual average temperature. For climate change scenarios, with the exception of sorghum, the other two crops considerably reduce the proportion of agricultural land area with some degree of aptitude for these. Increasing the annual mean temperature to values above the threshold at which corn and wheat crops are grown is the main cause of loss of aptitude. The determination of the degree of change associated with climate change can be used to develop public policies to address the problem of decreasing or losing the development capacity of crops.